2022
DOI: 10.3389/fmicb.2022.851011
|View full text |Cite
|
Sign up to set email alerts
|

Extracytoplasmic Function Sigma Factors Governing Production of the Primary Siderophores in Pathogenic Burkholderia Species

Abstract: Bacteria respond to changing environments by modulating their gene expression programs. One of the mechanisms by which this may be accomplished is by substituting the primary σ factor with an alternative σ factor belonging to the family of extracytoplasmic function (ECF) σ factors. ECF σ factors are activated only in presence of specific signals, and they direct the RNA polymerase (RNAP) to transcribe a defined subset of genes. One condition, which may trigger the activation of an ECF σ factor, is iron limitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Most of the virulence factors expressed under infection conditions were found to be upregulated during C. elegans infection and are mostly related to processes regarding bacteria sensing and interaction with the surrounding environment. Two of the those genes were the extracytoplasmic function sigma factors orbS and ecfD, which in Burkholderia species are activated by iron limitation conditions, managing the production and secretion of siderophores, which chelate iron and facilitate its cellular uptake, constituting an important mechanism for bacterial virulence (Grove 2022). The genes that code for the Hfq chaperone and the LysR family protein ShvR, two pleiotropic regulators, were found to be dysregulated in B. cenocepacia J2315 during C. elegans infection (Supplemental Table S6).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the virulence factors expressed under infection conditions were found to be upregulated during C. elegans infection and are mostly related to processes regarding bacteria sensing and interaction with the surrounding environment. Two of the those genes were the extracytoplasmic function sigma factors orbS and ecfD, which in Burkholderia species are activated by iron limitation conditions, managing the production and secretion of siderophores, which chelate iron and facilitate its cellular uptake, constituting an important mechanism for bacterial virulence (Grove 2022). The genes that code for the Hfq chaperone and the LysR family protein ShvR, two pleiotropic regulators, were found to be dysregulated in B. cenocepacia J2315 during C. elegans infection (Supplemental Table S6).…”
Section: Discussionmentioning
confidence: 99%
“…At first sight, a postranscriptional mechanism regulates its disruption to supply the 65 kDa protein, which is recognized by the same antibodies as the 70-kDa isoform ( Figure 2C ). Possibly the 70-kDa protein is a precursor of the 65- kDa protein, its production could be a consequence of the protein processing favored by Fur de-repression, or from mechanical disruption, rather than a change in the use of the transcription start site ( Duval et al, 2017 , Grove, 2022 ). Mass spectrometry analysis showed that amino-terminal amino acids were maintained in both the 65-kDa and 70-kDa proteins, demonstrating the presence of both isoforms of the protein.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, it is assumed that the number of ECF σs increases in relation to genome size and the complexity of bacterial environment. 37,54,55 If L. interrogans has different σ factors with unique promoter preferences, it can use them, making regulatory decisions in response to a change in environment or cellular state for survival. Accordingly, more than 30 genes encoding σ factor regulators have also been found in the L. interrogans genome, including anti-σ factors and anti-σ factor antagonists 60 (Table 3).…”
Section: Factorsmentioning
confidence: 99%
“…Interestingly, the number of ECF σs encoded within the bacterial genomes is different and reflects the likelihood that the bacterium will encounter changing environmental conditions; on average, bacterial genomes contain 6 ~ 10 genes encoding ECF σs. 37,54,55 However, there are also phyla particularly ECF-rich which contain 40-50 ECF σs per genome (Acidobacteria, Actinobacteria and Bacteroidetes) (Staroń et al 2009). Conversely, for example, the genera of Borrelia (also Spirochaetes) and Mycoplasma (Firmicutes), which are pathogens with small genomes (>2 Mb), do not possess any ECF σs (Staroń et al 2009).…”
Section: Characteristics Of Eubacterial σ Factorsmentioning
confidence: 99%
See 1 more Smart Citation